Suicidal ideation, attempt and associated factors among people with cancer attending cancer center, eastern Ethiopia - Nigussie, Kabtamu; Tesfaye, Dejene; Abdisa, Lemesa; Tolosa, Lidiya; Bete, Tilahun; Gemechu, Kabtamu; Negash, Abraham; Sertsu, Addisu; Dereje, Jerman; Debele, Gebiso Roba; Dechasa, Deribe Bekele (Frontiers in Psychiatry, 2023)
Background Suicide is one of the most common public health problems and the second leading cause of death among individuals 15–29 years of age. Suicidal ideation and attempt are one of the common psychiatric emergence in patients with cancer that needs early detection and management before patients end their lives. Therefore, the aim of the study was to assess the magnitude of suicidal ideation, attempts, and associated factors among people with cancer in Eastern Ethiopia. Methods An institutional-based cross-sectional study design was conducted among 362 participants. A composite international diagnostic interview was used to evaluate suicidal ideation and attempt. Epi-Data version 4.6.2 was used for data entry, and SPSS version 20 was used for analysis. Logistic regression analysis was done to identify associated factors for both suicidal ideation and attempt. p-values less than 0.05 are considered statistically significant, and the strength of the association will be represented by an adjusted odds ratio with a 95% confidence interval. Results The magnitude of suicidal ideation and attempt among people with in this study was 22.9% [95% CI, 18.7–27.4] and 9.8% [95%CI, 6.7–12.8] respectively. Being living alone [AOR = 4.90, 95% CI, 2.08–11.90], and having depressive symptoms [AOR = 3.28, 95% CI, 1.37–7.73], female ([AOR = 1.53, 95% CI, 1.30–3.23], anxiety symptoms [AOR = 3.06, 95% CI, 1.35–6.73)] and having poor social support [AOR = 3.08, 95% CI, 1.72–5.05], were significantly associated suicidal ideation whereas, Being living alone [AOR = 2.89, 95% CI, 1.09–7.65], having a depressive symptoms [AOR = 4.88, 95% CI, 1.45–13.28], being divorced/widowed [AOR = 3.46, 95% CI, 1.09–10.09] and stage four cancer [AOR = 5.53, 95% CI 2.97–7.47] were significantly associated with suicidal attempt. Conclusion Nearly one-quarter and one-tenth of people with cancer have suicide ideation and attempt, respectively. Suicidal behavior among cancer patients was found in this study to be a common problem. Living alone, having depressive and anxiety symptoms, being a female, having poor social support, and being in forth stage of cancer were risk factors for suicide. Therefore, early screening, diagnosing, and treating suicide and its factors will be mandatory and expected from health care providers and non-governmental organizations.